CCL13 and human diseases - Li, Laifu; Dai, Fei; Wang, Lianli; Sun, Yating; Mei, Lin; Ran, Yan; Ye, Fangchen (Frontiers in Immunology, 2023)
CCL13/MCP-4 belongs to the CC chemokine family, which induces chemotaxis in many immune cells. Despite extensive research into its function in numerous disorders, a thorough analysis of CCL13 is not yet accessible. The role of CCL13 in human disorders and existing CCL13-focused therapies are outlined in this study. The function of CCL13 in rheumatic diseases, skin conditions, and cancer is comparatively well-established, and some studies also suggest that it may be involved in ocular disorders, orthopedic conditions, nasal polyps, and obesity. We also give an overview of research that found very little evidence of CCL13 in HIV, nephritis, and multiple sclerosis. Even though CCL13-mediated inflammation is frequently linked to disease pathogenesis, it’s fascinating to note that in some conditions, like primary biliary cholangitis (PBC) and suicide, it might even act as a preventative measure.